Retrieving the configuration of grain boundary structure in polycrystalline materials by extraordinary X‐ray reflection analysis. Issue 4 (16th July 2020) - Aarão-Rodrigues, Lorena; Isaac, Augusta; Figueiredo, Roberto B.; Malachias, Angelo
Abstract : Synchrotron X‐ray diffraction measurements performed on Mg samples allowed the retrieval of preferred configurations of grain boundary interfaces through the observation of weak diffraction peaks located between fundamental reflections. Kinematical simulations verifying possible interface structures established the correspondence of the non‐bulk peaks to grain boundary interfaces that may be less energetic than the usually investigated twin‐plane symmetric conditions. Abstract : The development of materials is strongly related to our capability of understanding thermal, mechanical and chemical processing on the nanoscale. Unravelling the interface structure is crucial for opening new regimes in property–performance space. Interface arrangements have been characterized by statistically limited microscopy techniques. In this work, a large‐angular‐range detector was used for synchrotron diffraction measurements on commercially pure Mg. Long acquisitions allowed the retrieval of preferred interface configurations through the observation of extraordinary diffraction peaks located close to the Mg 102, 200, 204 and 300 fundamental reflections. A kinematical simulation scanning possible interface structures established the correspondence of the non‐bulk peaks to the interfacial organization of atoms that may be responsible for their appearance. Simulated interfaces were probed for a wide range of angular displacements with respect to the main cleavage planes. The results indicate configurations that allow the observation of X‐ray diffraction, representing a long‐range‐ordered pattern of atomic distributions in Mg. The introduced methodology allows for nondestructive monitoring of systems that undergo processes that modify grain sizes and grain‐interface orientation.